Staphylococcus aureus carriage in selected kindergartens in Klang Valley - Mohamed N.A.; Ramli S.; Amin N.N.Z.; Isahak I.; Jamaluddin T.Z.M.T.; Salleh N.M.; Wan Shahida Wan Sulaiman (Malaysian Medical Association, 2024)
Indexed by Scopus